M Pengembangan Pompa Irigasi Pertanian Menggunakan Energi Listrik Tenaga Surya di Desa Duri, Slahung, Ponorogo - Didik Riyanto; Yoyok Winardi; Mohammad Muhsin (Institut Pertanian Bogor, 2021)
Community service program To develop agricultural irrigation is carried out in Duri village, Slahung sub-district, Ponorogo district. Agriculture in Duri village has been dependent on irrigation from the rain so agricultural activities only rely on the availability of water during the rainy season, while the potential for water from groundwater with a depth of 20 m has not been able to be utilized optimally because it is constrained by relatively expensive equipment and technology. For this reason, a community service program is carried out which aims to meet the irrigation needs of farmers. The method of implementing activities consists of an inventory of data related to the conditions and needs of materials to be applied with technology, technology design, technology application, training in the use of technology, and evaluation. The result of the activity is a program of implementing an irrigation pump with solar cell electricity that is applied to one of the farmer groups' fields, namely a water pump that is able to lift water from a depth of 20 m with a water discharge of 1080 L/hour and is able to last for 2 hours. able to meet water needs in the dry season and can be used to grow crops on a small scale such as vegetable crops on a land area of 100 m.